PENGARUH PENERAPAN GREEN ACCOUNTING DAN KINERJA LINGKUNGAN TERHADAP NILAI PERUSAHAAN PADA SEKTOR PERTAMBANGAN - Tifal Rahmawati; Retno Suwiyanti (Jurnal Akuntansi dan Keuangan Syariah - ALIANSI, 2025)
Green accounting, also known as environmental accounting, is accounting that involves environmental costs or budgets in company activities. Green accounting also identifies, presents, and discloses a company's environmental impact and performance. This study aims to analyze the effect of the application of independent variables—green accounting and environmental performance—on the dependent variable, firm value, in the mining sector listed on the Indonesia Stock Exchange and participating in PROPER for the 2019-2023 period. This study employed multiple linear regression with SPSS version 30 as the analytical tool. The data used in this study were secondary data in the form of annual reports from mining companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2023 period. A purposive sampling technique was used, resulting in seven sample companies. The results of this study indicate that both green accounting and environmental performance partially influence firm value. Simultaneously, both green accounting and environmental performance influence firm value.